Pengembangan Media Pembelajaran Wordwall Berbasisi IT Pada Materi Sistem Tata Surya Kelas IV SD - Sajidah, Masulla Hana; Desiningrum, Noviana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the lack of use of interactive media in science learning wich makes it difficult for students to understand abstract materials such as planetary movements. This study aims to determine whether Wordwall-based learning media is practical and effective in improving student learning outcomes. The subject of this study is Wordwall learning media designed for grade IV elementary school students. The method used is the ADDIE development model (Analysis, Design, Development, Implementation. Evaluation). Data collection techniques are carried out through literature studies of previous and relevant scientific sources. The data analysis technique used qualitative descriptive analysis of the result of literature studies and experts. The results of the study showed that the media developed met the criteria of very valid according to media experts and material experts, and was proven effective in improving student learning outcomes based on limited trials. Wordwall media provides interactive games that make it easier for students to understand concepts through visualization and active participation